The Transcendental Meditation Program's Impact on the Symptoms of Post-traumatic Stress Disorder of Veterans: An Uncontrolled Pilot Study. Issue 1 (29th December 2017) - Herron, Robert E; Rees, Brian
Abstract: Background: Current treatments for post-traumatic stress disorder (PTSD) are only partially effective. This study evaluated whether an extensively researched stress reduction method, the Transcendental Meditation (TM) technique, can reduce the PTSD symptoms of veterans. Previous research suggested that TM practice can decrease veterans' PTSD symptoms. Methods: A one-group pretest–posttest design was used to evaluate the impact of TM practice on reducing PTSD symptoms. A convenience sample of 89 veterans completed PTSD Checklist-Civilian (PCL-5) questionnaires. Among those, 46 scored above 33, the threshold for provisional diagnosis of PTSD, and were included in this evaluation. The PCL-5 measured PTSD symptoms at baseline and 30 and 90 d after intervention. Regularity of TM practice was recorded. Paired sample t -tests were used to assess within-group changes from baseline to post-intervention periods. Analysis of variance was used to compare full-dose (two 20-min TM sessions per day) and half-dose (one 20-min TM session per day) groups. Findings: After 1 mo of TM practice, all 46 veterans responded; their PCL-5 average decreased from 51.52 in the pre-intervention period to a post-intervention mean of 23.43, a decline of 28.09 points (−54.5%); standard deviation: 14.57; confidence interval: 23.76–32.41; and effect size: −1.93; p < 0.0001. The median PTSD scores declined from 52.5 to 22.5, a decrease of 30 points (−57%), while 40 veterans (87%) had clinically significant declines (>10 points) in PTSD symptoms, and 37 (80%) dropped below the clinical level (<33). At the 90 d posttest, 31 of the 46 responded and three more dropped below the 33 threshold. Intent-to-treat analyses revealed clinically and statistically significant effects. A dose–response effect suggested a causal relationship. The full-dose group exhibited larger mean declines in PTSD symptoms than the half-dose group. Averages of the 46 veterans' responses to 20 PCL-5 questions exhibited significant ( p < 0.0001) declines from the pre-intervention period to the 30-d post-intervention assessment. Discussion: Results indicated that TM practice reduced PTSD symptoms without re-experiencing trauma. Because of the magnitude of these results and dose–response effect, regression to the mean, spontaneous remission of symptoms, and placebo effects are unlikely explanations for the results. Major limitations were absence of random assignment and lack of a control group. Participants chose to start and continue TM practice and to complete PCL-5 questionnaires. Those who self-selected to enter this study may not be representative of all veterans who have PTSD. Those who did not complete follow-up questionnaires at 90 d may or may not have had the same results as those who responded. The design and sampling method affect the generalizability of the results to wider populations. When taking into account these results and all previous research on the TM technique in reducing psychological and physiological stress, the convergence of evidence suggests that TM practice may offer a promising adjunct or alternative method for treating PTSD. Because of the widely recognized need to identify effective new approaches for treating PTSD, randomized research with control groups is warranted to further investigate the effectiveness of TM practice as a treatment for PTSD.